SpongeBob SquarePants. SpongeBob's frozen face-off [videorecording (DVD)] (SpongeBob SquarePants (Television program), 2012)
More fun with SpongeBob and his friends as they get involved in sports such as racing and golf while Mr. Krabs deals with remodeling and new competition.